Evaluación del síndrome de Burnout en los trabajadores del cuerpo de bomberos en la Joya de los Sachas, periodo 2024 - Chacón Angamarca, Mario Jhair (2025)
The research was developed in the Joya de los Sachas fire department with the objective of evaluating the Burnout syndrome present in firefighters, in addition to correlating it with sociodemographic variables and contrasting the results with other studies in order to enrich the scientific knowledge on the subject, in addition to proposing mitigation strategies through the application of physical and mental exercises with an active break manual. The methodology applied in this work was first the collection of data through a Google Forms so that each firefighter enters their social and demographic profile, answering the MBI (Maslach Burnout Inventory) test, consisting of 22 items, affirmatively. The type of research was correlational, relating the sociodemographic variables with the 3 dimensions of Burnout and then entering the data into the SPSS V.27 software and interpreting the tables produced by the statistical program. A medium level of burnout syndrome was found in 81.3% of the fire department, while a low level was found in 18.8% of the fire department. No high levels were found. It can be concluded that medium-low levels of burnout were found within the institution; that is, this syndrome is present, but not at high levels. To reduce these levels, an active break manual was presented based on three different techniques: joint movements, breathing exercises, and mental distraction exercises.